Relationship Between Spartina alterniflora Belt on Tidal Flats and Tidal Water Levels A Case Study on Jiangsu Coast and Hangzhou Bay, China - Jialin, Li; Xiaoping, Yang; Yiqin, Tong (2009)
Spartina alterniflora is one of the most extensive of the salt marsh vegetations on the mudflats of China. While it has important ecological functions in its native ecosystem such as maintaining the flats, reducing erosion, accelerating sedimentation and forming new land, as an alien species, it may displace native plants, threaten the native ecosystem and cause a decline in the richness of native species. Based on elevation measurements of some S. alterniflora sections and harmonic analysis of tides, we investigated the relationship between the elevation of S. alterniflora belt and tidal water levels. The results can be summarized as follows: (1) Tidal inundation accumulation frequency was a more reasonable index than other factors for describing the relationship between the elevation of S. alterniflora belt and tidal water levels. (2) The height of the seaward edge of the S. alterniflora belt was above mean sea water level, below mean high water level, with an approximate inundation rate of 21.1-28.4%. (3) Besides inundation rate, factors such as topography of the flats, tidal creek, granulate sizes of surface sediments, near-shore waves, salinity, climate and water pollution may also have an impact on the S. alterniflora belt and result in regional differences. (4) The impacts of incursion of the plant on the native ecosystem of the flats varied. The result on the relationship between the distribution area of the plant and tidal water levels has its potential application on different tidal flats that may be invaded by the plant. (5) The S. alterniflora salt marsh is sensitive to rises in global sea level and storm surge enhancement. The research on the response mechanism of S. alterniflora to global change is particularly important to secure the ecological pattern of key coastal regions.
Keywords: Grasses; Coastal plants